2021
DOI: 10.3389/frai.2021.668302
|View full text |Cite
|
Sign up to set email alerts
|

Topology Applied to Machine Learning: From Global to Local

Abstract: Through the use of examples, we explain one way in which applied topology has evolved since the birth of persistent homology in the early 2000s. The first applications of topology to data emphasized the global shape of a dataset, such as the three-circle model for 3 × 3 pixel patches from natural images, or the configuration space of the cyclo-octane molecule, which is a sphere with a Klein bottle attached via two circles of singularity. In these studies of global shape, short persistent homology bars are disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Subsequently the discussion has refined when it was shown that short and medium-length persistence intervals have the most distinguishing power for specific types of applications [8,81]. The current understanding is roughly that long intervals reflect the topological signal, and (many) short intervals can help in detecting geometric features [3]. We believe that our work brings new insight into this discussion.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Subsequently the discussion has refined when it was shown that short and medium-length persistence intervals have the most distinguishing power for specific types of applications [8,81]. The current understanding is roughly that long intervals reflect the topological signal, and (many) short intervals can help in detecting geometric features [3]. We believe that our work brings new insight into this discussion.…”
Section: Resultsmentioning
confidence: 77%
“…In the first decade after the introduction of PH, it was seen primarily as the descriptor of global topology. Recently, there have been many discussions and greater understanding that PH also captures local geometry [3]. However, it is still suggested that the long persistence intervals capture topology (as was the case with the detection of holes in Section 3), and many-even too many for the human eye to count-short persistence intervals capture geometrical properties (as was the case with curvature prediction in Section 4).…”
Section: Convexitymentioning
confidence: 99%
See 1 more Smart Citation
“…The homology groups in (1) have several advantages over distance-based persistent homology, but are generally difficult to compute, particularly in higher dimensions. One application of sublevel set persistence is to topological data analysis, which involves computing the superlevel set persistence of a suitable density estimator ρ (or the sublevel set persistence of − log(ρ)).…”
Section: Introductionmentioning
confidence: 99%
“…The higher dimensional case has been studied using the Morse-Smale complex [11] in the context of grayscale images, which has also been applied to topics such as energy landscapes in particle systems [14]. For other applications and references, see also [1,2,3,4,5,10,22].…”
Section: Introductionmentioning
confidence: 99%